PEDAGOGICAL CONDITIONS FOR TRAINING STUDENTS OF ENGLISH PHILOLOGY FOR USE OF INTERACTIVE TECHNOLOGIES IN THEIR FUTURE PROFESSIONAL ACTIVITY - Lypchanko-Kovachyk, Oksana (Social work and education, 2017)
General humanization of higher philological education provides the dynamics of the development of the professional potential of students of philological departments not only as holders of normative communication and language code, but also as a creative, psychologically stable people, who are capable to think creatively and assess pedagogical situations, using practically acquired learning experience of communication in the educational environment .A modern philology teacher must not only pass on the experience of the previous generations to the new generations, but also form an appropriate level of foreign language training for students, a desire for constant updating the knowledge, skills of self-education in the field of a foreign language, to be prepared for interaction with subjects of the foreign language environment, using for this purpose active teaching methods. This will be possible under the conditions if future philologists acquire knowledge, skills of using interactive technologies in the professional activity of a foreign language teacher. the process of preparing foreign language teachers to use interactive technologies in their professional activities can be understood as a set of interrelated activities that create pedagogical conditions, the implementation of which provides the formation of the phenomenon under study. In this context, there is a need to develop a model for preparing future philologists for the use of interactive technologies in professional activities.